2015
DOI: 10.1007/s11069-015-1772-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tsunami hazards in ports and their impact on marine vessels derived from tsunami models and the observed damage data

Abstract: This paper presents a detailed study of tsunami hazard in ports and its correlation with the damage suffered by marine vessels. The study aims to develop a new loss function to estimate the potential damage of marine vessels due to tsunami attack based on a novel multivariate statistical modeling method, which used several explanatory variables simultaneously to estimate an outcome or the probability of such outcome. In the first part of the paper, tsunami heights and velocities are numerically modeled by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…After the 2011 tsunami, Suppasri et al (2014) and Muhari et al (2015) developed fragility functions for fishing boats. Based on their results, the threshold water level and flow velocity values for the complete destruction of small boats of less than 5 t are 2 m and 1 m s −1 , respectively.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After the 2011 tsunami, Suppasri et al (2014) and Muhari et al (2015) developed fragility functions for fishing boats. Based on their results, the threshold water level and flow velocity values for the complete destruction of small boats of less than 5 t are 2 m and 1 m s −1 , respectively.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…The 2011 tsunami was numerically simulated using a set of nonlinear shallow-water equations, which were discretized using the staggered leap-frog finitedifference scheme (TUNAMI model;Imamura, 1996) with bottom friction in the form of Manning's formula, similar to previous studies Charvet et al, 2015;Macabuag et al, 2016). Six computational domains adopted from a previous study which used original data from the Geospatial Information Authority of Japan (GSI, 2015) were used as a nesting grid system of 1215 m (region 1), 405 m (region 2), 135 m (region 3), 45 m (region 4), 15 m (region 5), and 5 m (region 6).…”
Section: Simulation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Linear models that utilize linear least squares regression-most commonly applied in fragility studies (Tables 1 and 2), • GLM (e.g., Reese et al, 2011;Charvet et al, 2014a;Muhari et al, 2015;Macabuag et al, 2016a,b;De Risi et al, 2017a,b), • Generalized Additive Models (Macabuag et al, 2016a,b).…”
Section: Model Qualitymentioning
confidence: 99%
“…The average of the error rates for all iterations gives an estimate of the true prediction error rate [shown in (2)]. Cross validation has been used to estimate tsunami fragility curve prediction error rates by Muhari et al (2015) and Charvet et al (2014a, b), who also propose a penalised error estimation method [shown in (3)] for multinomial models such as those used in this study. In (3), N DS refers to the number of damage states (including DS0, no damage), and the predicted damage state (ds j,predicted ) for the jth observation is taken as the damage state that has the greatest probability of occurrence.…”
Section: It Is Recommended Thatmentioning
confidence: 99%